Partisipasi Pedagang Dalam Melakukan Pemilahan Sampah di Pasar Baru Kecamatan Tampan Kota Pekanbaru - Beny Yulianto (Jurnal Kesehatan Komunitas, 2016)
Garbage is defined as something that is not used anymore, unused, or something that is thrown away, which is derived from human activities and does not happen by itself. The market is one of the human activities that produce large amounts of garbage every day, when the waste sorting system is not good, it will make it difficult to carry out waste management and will have an impact on health directly or indirectly. This study aims to determine the factors associated with the participation of traders in waste sorting in Tampan Sub district Pasar Baru Pekanbaru.This study is quantitative research with cross sectional design. This research was conducted April 2015, sample in this study is 79 merchants. Data were collected by using questionnaires and observation. Data analysis for bivariate with chi-square test with 95% confidence level with Î± = 0.05. The results showed that there is a relationship between education (OR = 2,60 ; CI: 1,08-3,67), socialization (OR = 3,10; CI: 2,58-5,99) availability of trash waste (OR = 8,25 ; CI: 2,98-7,55 with waste sorting participation.